Peluang dan Tantangan Pesantren Salaf di Era Digital (Studi Kasus di PP. Fathul Ulum Kwagean) - Nasirudin, Ahmat (Lembaga Yasin AlSys, 2024)
Islamic boarding schools are the oldest educational institutions in Indonesia which still exist today. Although, there are indeed several Islamic boarding schools that used to be very successful but are now starting to decline. One of the reasons for this is that it has been eroded by developments over time and that a mature cadre system has not been prepared to continue managing Islamic boarding schools. One of the Salaf Islamic boarding schools that is still in existence today is PP. Fathul Ulum Kwagean. The aim of this research is to examine in more depth the opportunities and challenges of students at the Salaf Islamic boarding school, namely, the Fathul Ulum Kwagean Kediri Islamic Boarding School in the digital era. This research is descriptive qualitative field research. This research describes, tells and interprets a reality that is occurring in the field today. The results of this research that researchers obtained in the field were several challenges and opportunities that were felt in PP. Fathul Ulum Kwagean includes the use of Maktabah Syamilah as a digital library which is considered credible enough for developing studies, as a medium for preaching through social media so that the reach of preaching carried out by Islamic boarding schools is wider and can be felt by many groups, and several digital-based administrative systems. Meanwhile, the challenges faced by PP. Fathul Ulum Kwagean in this digital era is the beginning of a shift in several Islamic boarding school tendencies, from initially the education and learning process in Islamic boarding schools which was conservative or maintained old learning methods, the spread of negative content that is easily accessible in the digital era, changes in external values and culture that are not appropriate with Islamic boarding school values, and the challenges of adapting for both the community and ustadz.